Implicações econômicas da internacionalização em casa: o caso de uma universidade pública com autonomia financeira - Cabral, Carolynne Borges (Universidade do Vale do Rio dos Sinos, 2023)
The aim of this work is to analyze how a financially autonomous public Higher Education Institution can economically enable the process of internationalization at home. To achieve this objective, the internationalization of higher education in Brazil was described, bringing some theoretical concepts regarding Home Internationalization. As it is a municipal public educational institution with administrative, budgetary, and financial autonomy, it has some peculiarities because its maintenance and operation are the responsibility of the institution itself. Therefore, tuition fees are charged to students, but for the procurement and hiring processes, it is necessary to adhere to the legality required for public entities. From this point, internationalization becomes a necessary path, and since the Higher Education Institution currently only offers academic mobility, this study presents means to enable Home Internationalization at an educational institution that is obligated to sustain itself, but within the framework of municipal public power, with transparency and compliance with all legal requirements regarding the allocation of public funds. The research is a unique case study, and the data were collected through document analysis and interviews with six of the employees involved in any type of procurement and hiring within the Higher Education Institution. These individuals included an internationalization specialist, a representative from the procurement department, a lawyer, a member of the senior administration, someone from the financial department, and an external representative from one of the municipal public regulatory bodies. The researcher also conducted direct observations. After data collection, the content was analyzed using content analysis techniques. The results indicate that there is the possibility and interest from the management to invest in the internationalization of the Higher Education Institution, requiring a mapping of the actions to be taken to assess the costs and other measures needed to facilitate this process, such as the creation of a language center, internationalization-focused events, among others. The main barrier identified was the time required for the execution of processes, as all legal aspects needed to allocate public resources for each internationalization-related action must be verified, while maintaining the transparency required for municipal public entities.
Keywords: Instituição de ensino superior; internacionalização em casa; internacionalização do ensino superior; Universidade; Instituição pública municipal com autonomia financeira; Higher education institution; Internationalization at home; Internationalization of higher education; University; Municipal public institution with financial autonomy; ACCNPQ::Ciências Sociais Aplicadas::Administração